2007
DOI: 10.1590/s1519-69842007000300022
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of Macrobrachium amazonicum females (Crustacea, Palaemonidae)

Abstract: Macrobrachium amazonicum is considered a favorite Brazilian species of freshwater prawn for cultivation as a result of its quick development and because it is easy to maintain in captivity. The aim of this work is to describe the sexual cycle stages and determine maturation age of the female M. amazonicum, which was collected monthly from June, 2002 to May, 2003 in the Jaguaribe River, Itaiçaba, Ceará. A monthly sample of water was also collected to determine the following parameters: temperature, dissolved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
29
4
24

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 15 publications
14
29
4
24
Order By: Relevance
“…Overall sex-ratio of M. amazonicum that did not differ significantly from the expected 1:1 was also verified by Flexa et al (2005), Sampaio et al (2007) and Silva et al (2007). The ovigerous females of M. amazonicum were found throughout the year; indicating continuous reproduction, as also observed by Odinetz-Collart (1991) in the lower Amazon region, Peixoto (2002), Lucena-Frédou et al (2010) and Freire et al (2012).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Overall sex-ratio of M. amazonicum that did not differ significantly from the expected 1:1 was also verified by Flexa et al (2005), Sampaio et al (2007) and Silva et al (2007). The ovigerous females of M. amazonicum were found throughout the year; indicating continuous reproduction, as also observed by Odinetz-Collart (1991) in the lower Amazon region, Peixoto (2002), Lucena-Frédou et al (2010) and Freire et al (2012).…”
Section: Discussionsupporting
confidence: 58%
“…This pattern diverges from several studies that reported a peak in reproduction only in the rainiest seasons in different regions of Brazil, as well as in other Amazon regions (Odinetz-Collart, 1991), Northeast (Bragagnoli and Grotta, 1995;Sampaio et al, 2007), Midwest (Porto, 1998) and South (Bialetzki et al, 1997). Several environmental factors contribute to reproduction of estuarine shrimp, such as temperature, sediment, salinity and rainfall (Pinheiro and Hebling, 1998).…”
Section: Discussioncontrasting
confidence: 56%
“…Continuous reproduction pattern was also observed by other congener species in the Brazilian territory: Sampaio et al (2007) iheringi. There is certainly a variety of proximate and ultimate factors, e.g., water quality, water temperature, rainfall or water flow, availability of larval food, which may influence the reproductive period.…”
Section: Reproductive Periodsupporting
confidence: 53%
“…According to the characteristics shown by these bands, they may be considered good markers able to diagnose Mj and Ma, syntopic species that show taxonomic identification difficulties based only on morphological characteristics, due to the high level of morpho-logical similarity between these two species. Furthermore, according to studies conducted by Taddei et al (2006) and Sampaio et al (2007), there is ample diversity in size among the individuals of the same population and also among different populations, depending on environmental variations, which can hinder their identification even more.…”
Section: Discussionmentioning
confidence: 99%